Golden Triangle-Based Digital Learning Facility Management Model (Technology, People, Process) - Syukri Indra; Zahra Khusnul Lathifah; Abdul Kholik (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The rapid advancement of digital technology has transformed educational practices, requiring institutions to adopt effective digital learning systems. However, significant challenges remain, particularly in Islamic educational institutions, where limitations in technological readiness, human resource capacity, and management processes hinder optimal implementation. This study addresses the lack of an integrated framework by examining digital learning management through the golden triangle model, which consists of technology, people, and process. Using a qualitative multi-case study approach, this research was conducted in two Madrasah Aliyah Negeri in Bogor City. Data were collected through in-depth interviews, field findings, and documentation, and analyzed using the Miles and Huberman model supported by NVivo. The findings reveal that effective digital learning management is achieved through the synergy of three key components. The technology component includes blended learning, online learning, and classroom-based digital tools that support flexible learning environments. The people component highlights the collaborative roles of stakeholders, including school leaders, teachers, IT personnel, students, parents, and government institutions. Meanwhile, the process component reflects a structured managerial cycle involving policy, planning, organizing, implementation, and supervision supported by adequate infrastructure. Cross-case analysis indicates consistent implementation patterns across both research sites. These findings imply that successful digital learning in madrasah education requires a balanced and integrated management approach rather than isolated improvements in individual components. The study provides a conceptual and practical framework that can guide policymakers, school leaders, and educators in strengthening digital learning systems. Furthermore, it emphasizes the importance of aligning technological innovation with organizational capacity and educational values, particularly in the context of Islamic education, to ensure sustainable and effective digital transformation.